2021
DOI: 10.1590/1678-4685-gmb-2020-0147
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations after induced pluripotent stem cells reprogramming

Abstract: Induced pluripotent stem cells (iPSCs) are generated from adult cells that have been reprogrammed to pluripotency. However, in vitro cultivation and genetic reprogramming increase genetic instability, which could result in chromosomal abnormalities. Maintenance of genetic stability after reprogramming is required for possible experimental and clinical applications. The aim of this study was to analyze chromosomal alterations by using the G-banding karyotyping method applied to 97 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…At least 50 photomicrographs of metaphase cells were taken for karyotype analysis. Results indicated that the number of chromosomally atypical cells in the hUCMSCs sample was low (Table 2), affirming the genetic stability of hUCMSCs [28].…”
Section: Karyotype Analysis and Identificationmentioning
confidence: 73%
“…At least 50 photomicrographs of metaphase cells were taken for karyotype analysis. Results indicated that the number of chromosomally atypical cells in the hUCMSCs sample was low (Table 2), affirming the genetic stability of hUCMSCs [28].…”
Section: Karyotype Analysis and Identificationmentioning
confidence: 73%
“…After reprogramming, hiPSCs regain pluripotency capacity and express proliferation and pluripotency markers like SSEA4, OCT3/4, and Ki67 (Figure 4) 38 , 39 , 40 . It is known that reprogramming, as well as the lengthy culture of hiPSCs and differentiation, can lead to an abnormal karyotype, or rather induce mutations 41 . Therefore, the genetic background of the cultured cells should be monitored over time and at different passages by g-banding and whole exome sequencing.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Maintenance of genetic stability after reprogramming is required for possible experimental and clinical applications. iPSC lines may show clonal and non-clonal chromosomal aberrations in several passages (from P6 to P34), but these aberrations are more common at of cell cultures in later passages ( Vaz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%